DEVELOPING CREATIVE AND TECHNOLOGICAL COMPETENCIES THROUGH BLENDED LEARNING APPROACHES - Sharipova Gulshoda Bahriddinovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines how blended learning approaches can enhance students’ creative and technological competencies. By integrating traditional classroom instruction with digital learning tools, blended learning provides a flexible, interactive, and engaging educational environment. The study highlights that combining face-to-face activities with online platforms fosters problem-solving, innovative thinking, and technological skills. Understanding the benefits of blended learning helps educators design strategies that simultaneously support creativity and technological development.